Asymmetric Synthesis of Triaryl‐Substituted Chromans with Multiple Stereogenic Centers by [4+2] Cycloaddition Reaction. Issue 43 (15th November 2019) - Zhang, Heng; Liu, Guofeng; Guan, Xukai; Gao, Jigang; Qin, Xiangshuo; Jiang, Guofeng; Sun, Dongyang; Zhang, Guangliang; Zhang, Suoqin
Abstract : Asymmetric synthesis of triaryl‐substituted chromans with multiple adjacent stereogenic centers is described here. [4+2] formal oxa ‐Diels‐Alder cycloaddition of 1‐styrylnaphthols and in‐situ‐generated o ‐quinone metheides could proceed smoothly in the presence of H8 ‐BINOL‐type chiral imidodiphosphoric acids as catalyst. This method provides an efficient strategy to construct chiral chroman frameworks in high yields (up to 93 %) with excellent stereoselectivities (> 19:1 dr.) and enantioselectivities (up to 99 % ee ). Abstract : Triaryl‐substituted chromans were synthesized via enantioselective oxa ‐Diels‐Alder reaction catalyzed by chiral imidodiphosphoric acids. A variety of substitution patterns were achieved with high yields (up to 93 %) and excellent stereoselectivities (> 19:1 dr.) and enantioselectivities (up to 99 % ee).